Vereda and Murundu wetlands and changes in Brazilian environmental laws: challenges to conservation - Rosolen, Vania [UNESP]; Oliveira, Diego Alves de; Bueno, Guilherme Taitson (Springer, 2015)
Vereda and Murundu wetlands are widespread in the Cerrado (Brazilian savannah). The wetlands occupy topographic depressions on the flat plateau, which are permanently or seasonally waterlogged, with topsoil that has high contents of organic matter and endemic fauna and flora. These systems are important for regulating the water flux in the riverine network. Despite their environmental importance, the wetlands are largely neglected in planning policy, environmental legislation and scientific research, resulting in their degradation by the expansion and intensification of agriculture. In the studied catchment, a typical tropical savannah landscape and a region of typical agribusiness land use in the state of Minas Gerais was considered, where the Vereda and Murundu ecosystems are completely surrounded by agriculture. The transition zone between dry and wet soils is the most fragile and susceptible to degradation because it is subjected to the continuous expansion of land tillage. If the agribusiness model deployed in the region is responsible for the increase in wetland destruction, then changes in regulatory laws to define and preserve permanent preservation areas in the Brazilian Forest Code, for the years 1934, 1965, 1989 and in the two versions from 2012, are an impediment to the effectiveness of forest and wetlands protection and the policy of sustainable development.
Keywords: Wetlands; Vereda and Murundu; Cerrado; Forest code